A study on efectiveness in using continuous integration and development for software development: a state of the art review - Shah, Asadullah; Azizan, Adiz Nabawi (IIUM Press, 2020)
The purpose of this paper is to help in providing insight on the effectiveness in using continuous integration in software development. The aim of the study is achieved using the help of existing journal and article, theories and literature review of effectiveness in implementing the continuous integration. Design Approach - A total of 17 journals and articles including literature review have been analysed using state of the art literature review methodology. Search keywords that have been used are continuous integration, continuous deployment, software development + Jenkins. The main databases that we use are mostly IEEE (ieee.org) and articles of webpages. We focus on software development and include all the related based on software development. Currently the databases are based on the access provided by the university so we excluded all the paid databases that university does not have access to. Findings – Due to limited resources and cost, the review is limited to software development but provides possibilities for future research in different sectors such as industries that required automation in their work. We also found out that continuous delivery became popular in the current year as there is a rise of software and applications due to the booming mobile technology. Problem Statement – Even with the growth of technology, some organizations still depend on the traditional method. This is because of the lack of expertise and no budget. Continuous integration already exists in over a decade, but the implementation is not widely introduced.